Heat transfer and nanofluid flow characteristics in microchannel heat sink with different shapes - Kadhim, Altayyeb Abdullah (2013)
The main aim of this study is to enhance the cooling performance of MCHS by using conventional fluid, nanofluids and different cross-section shapes including hexagon,circular and rhombus MCHS. Microchannel heat sink (MCHS) has the most common and cost-effective hardware employed for the thermal management of Micro-Electro- Mechanical systems (MEMS) devices. The small channels of the Microchannel heat sink hydraulic diameter provided a high heat transfer coefficients. Geometry parameters of the channels like width and height are supposedly to have a significant effect on the laminar heat transfer and liquid flow in MCHS (Gunnasegaran et al. 2009). In this study, a numerical investigation of liquid laminar flow and heat transfer in different cross-section shapes microchannel heat sink using water and different types of nanofluids was studied. The upper wall is heated while the bottom wall and sides are adiabatic. Four types of nanofluids (Al2O3, CuO, SiO2 and ZnO with pure water) with different nanoparticles volume fraction (1%, 2%, 3% and 4%) and various nanoparticles diameter (25, 40, 55 and 70 nm) were used. In addition, the effect of using different types of base fluid which are ethylene glycol (C2H4(OH)2), Engine oil , glycerin (C3H5(OH)3) and water in MCHS with the nanofluids was also analyzed. This investigation cover Reynolds number and heat flux ranged from 100 – 1000 and 100 – 1000 kW/m2, respectively. The three-dimensional (3D) MCHS governing equations for both heat transfer and liquid flow were resolved by using Finite Volume Method (FVM). Model geometries have been drawn and meshed in GAMBIT 2.3 and simulations have been performed in commercial CFD cods FLUENT 13. The results show that the MCHS cooling performance was greatly influenced by the shapes of the channels crosssection and nanofluids. The best heat transfer performance was obtained in the rhombus cross-section MCHS by using Al2O3-H2O nanofluids as a working fluid at 4% particle volume fraction and 25 nm nanoparticles diameter.